Pengaruh Sosialisasi Pajak, Pemahaman Pajak, Sanksi Pajak, dan Persepsi Efektifitas Sistem Perpajakan Terhadap Kepatuhan Wajib Pajak UMKM (Survei pada Wajib Pajak UMKM di KPP Pratama Kebon Jeruk Satu) - Julia Endah Triyaningsih; Rokhanah Murkana (Jurnal Pena-Mas Akuntansi, 2022)
This study aims to to examine or determine the influence of tax socialization, understanding tax, tax sanction, and the effectiveness of the tax system on taxpayer compliance MSME. This research was conducted at MSME registered in KPP Pratama Kebon Jeruk Satu West of Jakarta. This research using quantitative approach, the data used are primary data, collected using questionnaires fill by respondents, chosen using probability sampling method, and sampling technique by simple random sampling. Population in this research is MSME. Data obtained from this research are 4.557 MSME and 100 samples of MSME use Slovin formula. This research uses data analysis using SPSS version 24.00 software. Data processed by using validity test, reliability test, classic assumption test, hypothesis test, test multiple linear regression analysis. The result of this study indicates that tax socialization, tax understanding, tax sanction, and the effectiveness of the tax system significantly influence on MSMEs taxpayer compliance in the KPP Pratama Kebon Jeruk Satu West of Jakarta.